The Effect of Giving Three Exercises on Reducing Pain for Low Back Pain Sufferers in Online Motorcycle Taxi Drivers - Gerhanawati, Ifa; Rakhmawati, Hafizah Sururul Nur; Ghurri, Ainul; Atmaja, Danuditya Purna; Ndayisenga, Japhet (Universitas Negeri Surabaya, 2025)
Purpose: Prolonged static sitting for ≥6 hours among online motorcycle taxi drivers increases lumbar load, reduces flexibility, and contributes to non-specific low back pain. This study aimed to determine the effectiveness of the Three Exercises program in reducing pain intensity in this population. Materials and Methods: This study used a randomized controlled trial (RCT) design involving 30 online motorcycle taxi drivers aged 22–60 years who met the inclusion criteria. Participants were randomly assigned to an intervention group receiving Three Exercises (knee to chest, pelvic tilting, and child pose) or to a control group. The intervention was performed 3 times per week for 12 weeks, with two sets of 10 repetitions per session, maintaining each position for 7 seconds with 3 seconds of rest. Pain intensity was measured using the Visual Analogue Scale (VAS) before and after the intervention. Statistical analysis used Wilcoxon paired tests and Mann–Whitney tests for between-group comparison. Result: The intervention group (n=15) showed a significant reduction in VAS scores from pretest (3.93 ± 1.48) to posttest (p = 0.001). The control group (n=15) also showed a more minor but significant reduction in VAS from 4.46 ± 1.06 (p = 0.025). The between-group comparison revealed a significant difference in posttest VAS values (p = 0.001), demonstrating superior improvement in the intervention group. Participant characteristics, including age, BMI distribution, work duration, and educational background, were comparable between groups. Conclusion: The Three Exercises program significantly reduces pain intensity compared with standard care in online motorcycle taxi drivers with low back pain. Its simple structure and feasibility support its use as an effective therapeutic exercise to improve lumbar comfort and functional capacity.